Using Dielectric Constant Measurement to Monitor Ethanol Fermentation and Anaerobic Co-Digestion of Lignocellulosic Biomass - Zoltán Péter Jákói; Balázs Lemmer; Réka Dobozi; Cecilia Hodúr; Sándor Beszédes (Fermentation, 2023)
Our study aimed to investigate the applicability of dielectric measurements across three key stages of plant-based biomass utilization: enzymatic hydrolysis of native and microwave pre-processed corn-cob residues, ethanol fermentation of the hydrolysates, and anaerobic co-digestion with meat-industry wastewater sludge. Our major findings reveal that microwave pre-treatment not only accelerates enzymatic hydrolysis but also improves sugar yield. A strong linear correlation (r = 0.987–0.979; R2 = 0.974–0.978) was observed between the dielectric constant and sugar concentrations, offering a reliable monitoring mechanism. During ethanol fermentation, microwave pre-treated samples resulted in higher yields; however, the overall bioconversion efficiency was lower. Dielectric measurements also exhibited a strong linear correlation (r = 0.989–0.997; R2 = 0.979–0.993) with ethanol concentration. Finally, anaerobic co-digestion could be effectively monitored through the measurement of the dielectric constants (r = 0.981–0.996; R2 = 0.963–0.993), with microwave-treated samples showing higher biogas yields. These results demonstrate that dielectric measurements provide a promising alternative for monitoring and controlling biomass utilization processes.